Impact of changing nozzle profiles on thermal and structural loads acting on nozzle wall. Issue 1 (1st July 2022) - Saleh, M; Saleh, S; Zayed, A
Abstract: A nozzle of rockets is a window for the combustion chamber to the ambient air. It is subjected to several thermal and mechanical loads acting on the internal wall. So, the nozzle structural behavior has a significant impact on the mission achievement. The aim of this paper is studying a variety of nozzle profiles shape and its influences on structural behavior. Computational fluid dynamics software was applied to investigate the temperature and pressure on the internal wall of the nozzle while observing if there is any change at nozzle ballistic performance or not. Four different convergent profiles had been investigated to study its effect on structural stresses acting on nozzle wall. The results showed body temperature distribution, static pressure and thermal-structural stresses at nozzle wall. Changing the internal profile of the nozzle convergent caused significant change in pressure and temperature loads acting on nozzle wall structure. Conical shape convergent profile produced less stresses at throat section by 19.8% compared to original profile.